2021
DOI: 10.1021/acs.joc.1c00861
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Catalyzed Methylthiolative Annulation of 2-Alkynyl Biaryls with DMSO: A Metal-Free Approach to 9-Sulfenylphenanthrenes

Abstract: An iodine-catalyzed sustainable, cost-effective, and atom-economic synthetic methodology is developed to synthesize a wide variety of valuable sulfenylphenanthrenes and polycyclic heteroaromatics in moderate to high yield through electrophilic thiolative annulation of 2-alkynyl biaryls (6-endo-dig cyclization) using methyl sulfoxides such as dimethyl sulfoxide (DMSO) as the sulfur source under transition-metal-free conditions. The transformation requires only iodine in a catalytic amount and trifluoroacetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Based on the above experimental results and previous reports, a plausible mechanistic pathway for this reaction was postulated (Scheme ). First, the reactive electrophilic intermediate I , rather than the previously presumed analogous CHF 2 SOTf and BnOTf, , was generated from the reaction of difluoromethyl sulfoxide and Tf 2 O.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Based on the above experimental results and previous reports, a plausible mechanistic pathway for this reaction was postulated (Scheme ). First, the reactive electrophilic intermediate I , rather than the previously presumed analogous CHF 2 SOTf and BnOTf, , was generated from the reaction of difluoromethyl sulfoxide and Tf 2 O.…”
mentioning
confidence: 56%
“…Given that sulfoxides have been verified to be versatile sulfur reagents in organic synthesis, we conceived whether sulfoxide containing CF 2 H can be developed as a powerful difluoromethylthiolating agent for the construction of SCF 2 H substituted products. In the pioneering work of the Procter group, bench-stable trifluoromethyl sulfoxide has been synthesized and used as a trifluoromethylthiolating reagent for installing the SCF 3 group onto nucleophilic (hetero)­arenes through an interrupted Pummerer reaction (Scheme a) .…”
mentioning
confidence: 99%
“…In 2020, the Z-selective synthesis of 2-methylthio-1,4-enediones 154 via visible-light catalysed methylthiolation of methyl ketones 82 with DMSO was presented by Deb, Baruah et al 76 The reaction was performed using 0. In 2021, Chatterjee's group 77 reported that various valuable methylphenanthrenes were obtained through an I 2 -catalyzed electrophilic thiolative annulation of 2-alkynyl biaryls (6-endodig cyclization) with DMSO, which acted as a methylthiolating reagent, oxidant, and solvent. For the mechanism, initially, MeSH was generated in situ through the decomposition of DMSO with the aid of TFAA.…”
Section: Methylthiolation Through a Mesi Intermediatementioning
confidence: 99%
“…In 2021, Chatterjee's group 77 reported that various valuable methylphenanthrenes were obtained through an I 2 -catalyzed electrophilic thiolative annulation of 2-alkynyl biaryls (6- endo-dig cyclization) with DMSO, which acted as a methylthiolating reagent, oxidant, and solvent. For the mechanism, initially, MeSH was generated in situ through the decomposition of DMSO with the aid of TFAA.…”
Section: [I] Mediated Methylthiolationmentioning
confidence: 99%
“…In this regard, iodine is considered as an effective catalyst compared to other Lewis and Brønsted acids, and transition metals. [18] A number of iodine-catalyzed reactions, including condensations, [19] dehydrations, [20] Michael additions, [21] lactonizations, [22] Paal-Knorr pyrrole formation, [23] the Hofmann-Löffler reaction, [24] C(sp 3 )À H fluorination, [25] and annulations [26] have been reported. However, no reports for the direct construction of quinolines and 1-azaxanthones bearing diverse functionalities, including alkyl groups or halogens, and carbonyl groups at the 3-positions of the benzene and pyridine rings have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%